Mesenchymal stem cell therapy promotes the improvement and recovery of renal function in a preclinical model - Urt-Filho, Antonio; Oliveira, Rodrigo Juliano; Hermeto, Larissa Correa [UNESP]; Pesarini, Joao Renato; David, Natan de; Cantero, Wilson de Barros; Falcao, Gustavo; Marks, Guido; Milan Brochado Antoniolli-Silva, Andrcia Conceicao (Soc Brasil Genetica, 2016)
Acute renal failure (ARF) is an extremely important public health issue in need of novel therapies. The present study aimed to evaluate the capacity of mesenchymal stem cell (MSC) therapy to promote the improvement and recovery of renal function in a preclinical model. Wistar rats were used as the experimental model, and our results show that cisplatin (5mg/kg) can efficiently induce ARF, as measured by changes in biochemical (urea and creatinine) and histological parameters. MSC therapy performed 24h after the administration of chemotherapy resulted in normalized plasma urea and creatinine levels 30 and 45d after the onset of kidney disease. Furthermore, MSC therapy significantly reduced histological changes (intratubular cast formation in protein overload nephropathy and tubular hydropic degeneration) in this ARF model. Thus, considering that current therapies for ARF are merely palliative and that MSC therapy can promote the improvement and recovery of renal function in this model system, we suggest that innovative/alternative therapies involving MSCs should be considered for clinical studies in humans to treat ARF.
Keywords: bone marrow; chemotherapy; nephrotoxicity; kidney disease; tissue regeneration